Analysis of the loading conditions and lubrication systems bearing slide mechanisms timing of internal combustion engine. - Вельбой, В.П.; Диха, К.О.; Бабак, О.П. (Problems of Tribology, 2016)
Velboj V.P., Dykha K.O., Babak O.P. Analysis of the loading conditions and lubrication systems bearing slide mechanisms timing of internal combustion engine.The analysis of the structural features of the bearing units of the timing of modern internal combustion engines according to the terms of the enabling load balancing, and lubrication. Set the cyclic mode of loading bearing supports depending on the operating cycle of the engine.Keywords: combustion engine, valve gear, bearing, cyclic loading, lubrication.